Action on Administrative Violations of General Elections by the General Elections Supervisory Body - Putu Eva Ditayani Antari; I Gede Druvananda Abhiseka; Michael Kennedy Robenson; I Gusti Ayu Eviani Yuliantari (Faculty of Law, University of Merdeka Malang, 2025)
Administrative and criminal violations frequently occur during general elections, despite the presence of institutions mandated to prevent and address such misconduct. These violations are not limited to election day but often arise earlier, particularly during the campaign period. The range of electoral offenses is broad, encompassing both criminal and administrative infractions. This study aims to analyze how the Election Supervisory Body responds to administrative violations in the electoral process. Using normative legal research, the study explores the regulatory framework governing these violations as outlined in Law Number 7 of 2017 on Elections. It also examines the procedures employed by the Election Supervisory Body in handling administrative violations, including those categorized as structured, systematic, and massive (TSM), in accordance with existing legal provisions. These mechanisms are designed to ensure that all administrative violations are addressed fairly and in line with applicable laws. Effective enforcement of these procedures supports the realization of transparent, impartial, and democratic elections.